HOW BIG IS THE INFLUENCE OF E-MARKETING ON INDONESIAN TOFU ENTREPRENEURS? - Agustina, Yuli; Winarno, Agung; Ichwanto, Mohammad Aris (International Journal of Innovative Technologies in Social Science, 2022)
The COVID-19 pandemic has had a negative impact on MSMEs, MSMEs have difficulty in marketing their products due to the social distancing policy. This program aims to revitalize and assist tofu producers in Kampoeng Tahu, Tinalan Village, with regards to product marketing by implementing a marketing-system. This program is designed to increase the productivity and income of producers, who in this digital era no longer rely solely on offline marketing. Therefore, tofu producers require the highly effective marketing tool of e-marketing. Because in the present day, everyone from young people to their parents shop online using social media. The social media that are often used and applied in this work program are Instagram and Shopee. There were five tofu producers who were the primary targets of the implementation of e-marketing socialization and training.